Penguatan Kompetensi Pendidik PAUD Melalui Pelatihan Model Pembelajaran DEDEn-PjBL Berbasis Clay Art - Sadaruddin Sadaruddin; Nasaruddin Nasaruddin; Nirwana Nirwana; Ramlah Yusran; Syamsuardi Syamsuardi; Usman Usman; Hasmawaty Hasmawaty (Jurnal Pengabdian Masyarakat, 2026)
This Community Service activity aims to improve the competence of PAUD educators in Gantarang District, Bulukumba Regency, through the application of the DEDEn-PjBL (Design, Explain, Develop, and Evaluation-Project Based Learning) learning model based on Clay Art. This activity involved 20 PAUD educators from various kindergartens in Gantarang sub-district, Bulukumba Regency. The series of PKM activities included socialization of the importance of early childhood education (PAUD), training in planning, implementing, and evaluating project-based learning, workshops on the Clay Art-based DEDEn-PjBL model, and managerial training in managing PAUD institutions. The results of the activities showed a significant increase in participants' understanding of the importance of ECD, their ability to apply project-based learning models, creativity in using clay as a learning medium, and improved managerial competence in managing ECD institutions. Data analysis showed an increase in participants' understanding of the importance of ECD from 45% to 90%, an increase in the ability to design project-based learning from 30% to 85%, and an increase in the use of clay in learning from 20% to 80%. Managerial training also improved financial management skills from 40% to 75%. This activity made a real contribution to improving the quality of ECD education in Gantarang sub-district and is expected to be applied in other areas facing similar challenges..